HUBUNGAN ANTARA MANAJEMEN SARANA DAN PRASARANA DENGAN KUALITAS SARANA DAN PRASARANA DI SMA YA BAKII 01 KESUGIHAN - Khikmatul Khasanah (Jurnal Tawadhu, 2022)
This study aims to determine the relationship between facilities and infrastructure management with the quality of facilities and infrastructure at SMA Ya Bakii 01 Kesugihan, to determine the implementation of facilities and infrastructure management at SMA Ya Bakii 01 Kesugihan, to determine the quality of facilities and infrastructure at SMA Ya Bakii 01 Kesugihan. The population in this study were all 300 students. In this study, a sample of 143 people was taken because the population exceeded 100 people. This sampling uses a random technique where the sample is taken at random. The instrument used in this study is the Guttman scale on the management of facilities and infrastructure and the quality of facilities and infrastructure. The data analysis technique used is descriptive analysis to answer the implementation of infrastructure management and the quality of facilities and infrastructure at SMA Ya Bakii. Then, a Pearson product moment correlation analysis was conducted to determine whether there was a relationship between the management of facilities and infrastructure and the quality of facilities and infrastructure at SMA Ya Bakii 01 Kesugihan. Based on the descriptive results, the implementation of infrastructure management and the quality of facilities and infrastructure is at a moderate level. The results of the Pearson moment correlation analysis state that there is a significant relationship between infrastructure management and the quality of facilities and infrastructure. Found the value of tcount = 0.939 with ttable = 0.164. This means that there is a very high and significant level of close relationship because 0.939 > 0.164 and it can be concluded that H0 is rejected and Ha is accepted.